Early cholecystectomy following percutaneous transhepatic gallbladder drainage is effective for moderate to severe acute cholecystitis in the octogenarians. (March 2023) - Pan, Yu-Ling; Wu, Pei-Shan; Chen, Jung-Hsuan; Chen, Liang-Yu; Fang, Wen-Liang; Chau, Gar-Yang; Lee, Kuei-Chuan; Hou, Ming-Chih
Highlights: For patients aged ≥ 80 years with moderate to severe acute cholecystitis, the morbidity and mortality rates of cholecystectomy are not high. Early cholecystectomy (< 6 weeks) and delayed cholecystectomy (≥ 6 weeks) have similar rates in conversion surgery, perioperative complications, and operative mortality. Early cholecystectomy has lower risks of recurrent acute cholecystitis and further biliary events compared with delayed cholecystectomy. Abstract: Background: Acute cholecystitis (AC) is a life-threatening infectious/inflammatory disease in older patients. This study aimed to investigate the safety and optimal timing of surgery in patients aged ≥ 80 years with moderate to severe AC who received percutaneous transhepatic gallbladder drainage (PTGBD). Methods: From January 2008 to February 2021, 152 patients were retrospectively enrolled. Clinical outcomes were compared among patients who received laparoscopic cholecystectomy (LC), open cholecystectomy (OC), and conversion surgery, and between those who received early (< 6 weeks after PTGBD) and delayed cholecystectomy (≥ 6 weeks after PTGBD). Logistic regression analysis was used to identify risk factors for recurrent AC, further biliary events, conversion, and perioperative complications. Results: Sixty-seven patients underwent LC, 62 underwent OC, and 23 underwent conversion surgery. Operation-related complications and mortality rates did not differ among the types of surgery; however, LC group had shorter operative time than the other groups. Eighty-two patients underwent early cholecystectomy, while 70 underwent delayed cholecystectomy. There were no differences in operative time, operation-related complications, and mortality rates between the groups. However, higher rates of recurrent AC and biliary events were observed in the delayed cholecystectomy group (52.9% vs. 4.9% and 57.1% vs. 8.5%, p < 0.001). On multivariate analysis, delayed cholecystectomy was a significant risk factor for recurrent AC (odds ratio [OR] = 19.42, p < 0.001) and further biliary events (OR = 15.95, p < 0.001). Conclusions: Early cholecystectomy is recommended for patients aged ≥ 80 years with moderate to severe AC following PTGBD. Graphical abstract: Image, graphical abstract